Մինաս Թեքէլեան եւ Պէյրութի մէջ 1972ին իր հիմնած Թեքէլեան նախապատրաստական երաժշտանոցը - Արթինեան, Ռուպինա (տպ. Atlas)
Minas Tekelian, an orphan who grew up to become a well-known musician in Lebanon and the Middle East, in 1972, by his own initiative, without the help of any association or the state, founded the first preparatory music school of Lebanon, in Beirut, for beginners, to help them learn solfeggio, theory of music and to play an instrument before entering the National Conservatory of Music. A few years later, in 1975, the civil war broke out in Lebanon, which lasted till 1990, but the Tekelian Preparatory School of Music kept open its doors against all odds. The author of this paper narrates briefly the 15 years of the school (1975-1990) during which she taught at Tekelian music school as a piano teacher. The paper also highlights the echoes of the Armenian press about the newly founded music school; it describes its curriculum, programs of public auditions, teachers, and graduates. The paper includes testimonies of six graduates who became professional musicians. The paper includes an overview of the graduates, photos of documents and auditions, and finally Minas Tekelian’s biography, written by his wife Ovsanna.
Keywords: Հաղորդումներ; Թեքէլեան նախապատրաստական երաժշտանոց